The role of circadian clock in astrocytes: From cellular functions to ischemic stroke therapeutic targets - Zhang, Yuxing; Zhao, Xin; Zhang, Ying; Zeng, Fukang; Yan, Siyang; Chen, Yao; Li, Zhong; Zhou, Desheng; Liu, Lijuan (Frontiers in Neuroscience, 2022)
Accumulating evidence suggests that astrocytes, the abundant cell type in the central nervous system (CNS), play a critical role in maintaining the immune response after cerebral infarction, regulating the blood-brain barrier (BBB), providing nutrients to the neurons, and reuptake of glutamate. The circadian clock is an endogenous timing system that controls and optimizes biological processes. The central circadian clock and the peripheral clock are consistent, controlled by various circadian components, and participate in the pathophysiological process of astrocytes. Existing evidence shows that circadian rhythm controls the regulation of inflammatory responses by astrocytes in ischemic stroke (IS), regulates the repair of the BBB, and plays an essential role in a series of pathological processes such as neurotoxicity and neuroprotection. In this review, we highlight the importance of astrocytes in IS and discuss the potential role of the circadian clock in influencing astrocyte pathophysiology. A comprehensive understanding of the ability of the circadian clock to regulate astrocytes after stroke will improve our ability to predict the targets and biological functions of the circadian clock and gain insight into the basis of its intervention mechanism.